Development and Managerial Decision-Making in an Architectural and Construction Company Based on the «Six Thinking Hats» Method - Makatora, Dmytro; Kubanov, Ruslan; Kopchuk, Ivan (ІНЖЕК, 2025)
The article explores the implementation of Edward de Bono’s “Six Thinking Hats” method in the managerial practice of architectural and construction companies, which enables a significant improvement in the decision-making process. The authors analyse the relevance of this approach in the context of the modern architectural and construction industry, which faces numerous challenges such as legislative changes, fluctuations in material prices, intense competition, and technological innovations. The “Six Thinking Hats” method provides a multifaceted approach to situation analysis, allowing managers to consider problems from different perspectives: facts, emotions, logic, creativity, and process-oriented thinking. This promotes the adoption of more balanced and effective decisions that take into account various aspects of projects, including financial, environmental, and social dimensions. The article details the role of each “hat”: the white hat focuses on collecting objective data; the yellow highlights potential benefits; the black identifies risks and drawbacks; the red addresses emotions and intuition; the green stimulates creativity; and the blue organizes the thinking process. Such a structured approach helps prevent conflicts and fosters constructive team discussions. The authors emphasize that the application of the “Six Thinking Hats” method enhances employee motivation, as each team member feels that their opinion matters. In turn, this fosters team spirit and innovation, as participants have more opportunities to express their ideas and suggestions. The article also presents practical recommendations for implementing the method in architectural and construction companies. These include conducting training sessions for staff, forming working groups, applying the method regularly in decision-making processes, and evaluating its effectiveness. Particular attention is given to creating a favourable organizational culture that supports the active participation of all team members in the management process. Overall, the authors conclude that Edward de Bono’s “Six Thinking Hats” method has considerable potential to enhance the effectiveness of management activities in architectural and construction companies. Its systemic approach, focused on addressing diverse aspects and stimulating creative thinking, can become a key success factor in today’s dynamic market environment. Implementing this method can contribute to increasing a company’s competitiveness, promoting innovation, and strengthening its position both nationally and internationally. Keywords: “Six Thinking Hats” method, managerial decision-making, architectural and construction company, innovation, teamwork, management effectiveness, creativity.
Розробка та прийняття управлінських рішень менеджером архітектурно-будівельної компанії на засадах методики «Шість капелюхів»
У статті розглядається впровадження методики «Шість капелюхів» Едварда де Боно в управлінську практику архітектурно-будівельних компаній, що дозволяє значно покращити процес прийняття управлінських рішень. Автори аналізують актуальність застосування цього підходу в умовах сучасної архітектурно-будівельної галузі, яка стикається з численними викликами, такими як зміни в законодавстві, коливання цін на матеріали, жорстка конкуренція та технологічні новації. Методика «Шість капелюхів» забезпечує багатогранний підхід до аналізу ситуацій, дозволяючи менеджерам розглядати проблеми з різних точок зору: фактів, емоцій, логіки, креативності та управлінського мислення. Це сприяє ухваленню більш зважених і ефективних рішень, що враховують різноманітні аспекти проєктів, включно з фінансовими, екологічними та соціальними. У статті детально описано роль кожного з «капелюхів»: білий капелюх фокусується на зборі об’єктивних даних; жовтий акцентує увагу на можливих вигодах; чорний виявляє ризики та недоліки; червоний враховує емоції та інтуїцію; зелений стимулює креативність; синій організовує процес мислення. Такий структурований підхід дозволяє уникати конфліктів і сприяє конструктивному обговоренню в команді. Автори підкреслюють, що застосування методики «шість капелюхів» підвищує мотивацію співробітників, оскільки кожен член команди відчуває важливість своєї думки. Це, своєю чергою, сприяє розвитку командного духу та інноваційності, оскільки учасники процесу мають більше можливостей для висловлення своїх ідей та пропозицій. У статті також представлені практичні рекомендації щодо впровадження методики в архітектурно-будівельних компаніях. Серед них: проведення навчальних сесій для персоналу, формування робочих груп, регулярне застосування методики в процесі прийняття рішень, а також оцінка ефективності її використання. Особлива увага приділяється створенню сприятливої організаційної культури, що підтримує активну участь усіх членів команди в управлінському процесі. Загалом, автори доходять висновку, що методика «Шість капелюхів» Едварда де Боно має значний потенціал для підвищення ефективності управлінської діяльності в архітектурно-будівельних компаніях. Її системний підхід, орієнтований на врахування різних аспектів та стимулювання креативного мислення, може стати ключовим фактором успіху в умовах сучасного динамічного ринку. Впровадження цієї методики може сприяти підвищенню конкурентоспроможності компаній, розвитку інновацій та зміцненню їхніх позицій як на національному, так і на міжнародному ринку. Ключові слова: методика «Шість капелюхів», управлінські рішення, архітектурно-будівельна компанія, інновації, командна робота, ефективність управління, креативність.
Keywords: “Six Thinking Hats” method; managerial decision-making; architectural and construction company; innovation; teamwork; management effectiveness; creativity; методика «Шість капелюхів»; управлінські рішення; архітектурно-будівельна компанія; інновації; командна робота; ефективність управління; креативність; 005.53